Pathogenesis of varicose veins - lessons from biomechanics - Pfisterer, Larissa; König, Gerd; Hecker, Markus; Korff, Thomas (Vasa, 2014)
The development of varicose veins or chronic venous insufficiency is preceded by and associated with the pathophysiological remodelling of the venous wall. Recent work suggests that an increase in venous filling pressure is sufficient to promote varicose remodelling of veins by augmenting wall stress and activating venous endothelial and smooth muscle cells. In line with this, known risk factors such as prolonged standing or an obesity-induced increase in venous filling pressure may contribute to varicosis. This review focuses on biomechanically mediated mechanisms such as an increase in wall stress caused by venous hypertension or alterations in blood flow, which may be involved in the onset of varicose vein development. Finally, possible therapeutic options to counteract or delay the progress of this venous disease are discussed.